A Survey on Stream Ciphers for Constrained Environments - Jassim, Sameeh A.; Farhan, Alaa K. (2021 1st Babylon International Conference on Information Technology and Science (BICITS), 2021)
Lightweight ciphers are defined as symmetric ciphers. They could be categorized into stream and block ciphers. A stream cipher is faster and less complex than block ciphers so it is suitable with the Internet of Things (IoT). The IoT is composed of many interconnected constrained devices that share and exchange data and information among each other continuously. Therefore, IoT devices must ensure basic security characteristics to protect that information. In this paper, we will make a survey on a solution that used stream cipher in cryptography. This survey investigates a detailed flow of the stream ciphers such as algorithm design pattern, key size, internal state, throughput, the vulnerability in security, and the initial vectors for comparison among various types of stream ciphers from lightweight cryptographic solutions. The goals of this survey are to discover the most effective IoT protection solution and to look at lightweight cryptographic solutions by taking into account the constraints the IoT devices have, as well as how does researched symmetric key cryptographic solution analysis work. The conclusion is the Fruit stream cipher has good resistance to known attacks, whereas the Enocoro128 and F-FCSR stream ciphers have large throughputs, as well as a WG, Grain, and MICKEY-128 stream ciphers are faster and more suitable to constrained devices (e.g., IoT) than other studied algorithms.